"We Need to Know These Things": Use Cases for Combined Social and Clinical Data Among Primary Care-Based Clinical and Social Care Providers - Yuri Cartier; Caroline Fichtenberg; Karis Grounds; Nicole Blumenfeld; Laura Gottlieb; Danielle Hessler Jones (SAGE Publishing, 2024)
Introduction/Objectives: Primary care organizations are increasingly collecting data on patients' social risks, bringing forth an unprecedented opportunity to present combined health and social data that clinical and social care providers could leverage to improve patient care and outcomes. Little is known, however, about how these data could be used and what combinations of specific data elements are most helpful. We explored how primary care staff who provide clinical or social care services view potential benefits of and use cases for combined patient-level clinical and social data. Methods: We conducted qualitative interviews or focus groups with 39 social and clinical care providers representing 6 healthcare organizations in San Diego County, California. Interviews were transcribed and analyzed using a deductive thematic analysis approach. Results: Overall, both clinical and social care providers noted the value of access to both types of data. Participants highlighted 3 benefits from integrating social and clinical data. The data could: (1) offer providers a more holistic view of patients' circumstances; (2) strengthen their ability to tailor care to patients' medical and social conditions concurrently; and (3) enhance coordination across care team members. Interviewees cited specific examples of ways social and clinical data could be paired to improve care. Conclusions: Social and clinical care providers alike envisioned multiple uses and benefits of accessing combined individual-level clinical and social data, highlighting the potential for practice and policy innovations to facilitate access and uptake of combined data. Future research should focus on ways to increase accessibility of cross-sector data and evaluate the impact of care informed by combined data on patient social and health outcomes.